Expanded Aesthetics: Care, Attention, and the Everyday Plant - Vandsø, Anette; Shepherd, Nick (The Nordic Journal of Aesthetics, 2025)
This paper explores the intersections of care, attention, and aesthetics as they relate to everyday plants, proposing an expanded framework of aesthetic sensibility that moves beyond traditional notions of beauty and attentiveness. Drawing on avantgarde theories and Yuriko Saito’s concept of everyday aesthetics, the paper examines two artworks featuring “everyday plants,” specifically “weeds” and “houseplants.” It demonstrates how these artworks broaden or expand our perception and experience of plants. The paper argues that this “expanded” aesthetic sensibility that entangles historical, political, aesthetic, and economic concerns is emblematic of our climatically changing world. The overall goal of the paper is to uncover current changes in how we look at and understand plants as a culturally constructed category of beings.